The au pair - Rous, Emma (Berkley, 2019)
"An addictive, highly commercial suspense novel featuring a grand estate, terrible secrets, and a young woman who bears witness to it all. If V.C. Andrews, Kate Morton, and Lexie Elliot had a love child, Emma Rous and THE AU PAIR would be it. Seraphine Mayes and her twin brother Danny were born in the middle of summer at their family's estate on the Norfolk coast. Within hours of their birth, their mother threw herself from the cliffs, the au pair fled, and the village thrilled with whispers of dark cloaks, changelings, and the aloof couple who drew a young nanny into their inner circle. Now an adult, and mourning the recent death of her father, Seraphine begins to go through his belongings, when she uncovers a family photograph that raises dangerous questions. It was taken on the day the twins were born, and in the photo, their mother, surrounded by her husband and her young son, is beautifully dressed, smiling serenely, and holding just one baby. Who is the child and what really happened that day? Someone knows the truth, if only Seraphine can find her. The Au Pair" --